Consumption and Acceptability Pattern of 21 Evaluated Maize Hybrids for Fresh Maize Production in South-Eastern Nigeria - Okoli, Evans Ebuka (Journal of Agricultural Policy, 2020)
Purpose: Green (fresh) maize (Zea mays L.) provides food security and income to farmers especially when other crops are still in the field. However, research on green maize variety is scarcely reported in literature or information on the consumption or acceptability pattern of the developed maize hybrids. Unattractive colour, bad taste, kernel size and hard kernels are among factors that affect the level of fresh maize acceptability and subsequent consumption of genotypes in the South eastern part of Nigeria, therefore, the purpose of this work is to study the variation in sensory characteristics of hybrids generated from crosses between seven maize genotypes of two local varieties (Oka Mbaise and Oka Bende-white) and five improved varieties (DTMA-4, DMR-ESRY (POOL 18-SR), PVA SYM 8 F2 (PRO VIT A), POOL 66/ACR-91 SUWAN - 1- SR (QPM), DTMA - W, from IITA) was evaluated at the Centre for Agricultural Research, Federal University of technology Owerri and the sensory evaluation was done at different hostels in Umuchima, Ihiagwa and Centre for Agricultural Research, FUTO. Methodology: The methodology used in the field to develop these hybrids was the Randomized Complete Block Design (RCBD). Questionnaires were used to achieve the following palatability qualities measured; colour, kernel hardness, appeal, size and taste. The numerical scoring from the questionnaires was analysed using Genstat discovery 10th Edition. Results: The result of this work revealed that there were significant differences among the hybrids for kernel size and appeal. The cross between DTMA-4 and all other genotypes had the highest grain size (2.17) and was the most preferred by the respondents. The crosses between POOL 66/ACR-91 SUWAN - 1- SR (QPM) and Oka Mbaise; POOL 66/ACR-91 SUWAN - 1- SR (QPM) and Oka Bende-white; DTMA - W and Oka Mbaise; DTMA - W and Oka Bende-white; Oka Mbaise and Oka Bende-white had the hardest grain (3.00) and were least preferred by the respondents. Correlation matrix of the sensory evaluation revealed that grain size, colour and appeal were positively correlated while hardness was negatively correlated with appeal. Unique contribution to theory, policy and practice: In contribution to practice, the study recommends the cross OKA MBAISE X OKA BENDE-WHITE as it was highly preferred by the respondents.